COMMUNITY SERVICE: INTRODUCTION TO 3D PRINTING WORKSHOP FOR TEACHERS OF SMA NEGERI 9 YOGYAKARTA - Setiawan, Cahyo Luchy Abhista; Tanujaya, Venni; Parikesit, Kalki; Soedirdjo, Rahmat Santoso; Aryasatya, Brian Rajendra; Damayanti, Amelia; Rahmania, Rizky Astari; Aldhama, Shofa Aulia; Wulandari , Chandrawati Putri; Prihandana, Gunawan Setia (Universitas Airlangga, 2025)
The swift advancement of 3D printing technology has emerged as a significant innovation applicable across multiple domains. 3D printing is the method of fabricating three-dimensional items from digital models by incrementally layering materials. The integration of 3D printing in educational institutions can facilitate a more engaging and innovative learning environment for students. Implementing 3D printing can enhance students' creativity and critical thinking abilities, which are vital for navigating technological progress. The approach utilized in the 3D printing introductory curriculum entails showcasing the utility and possibilities inherent in 3D printing technology. This procedure proceeds by incorporating Computer Aided Design (CAD) software and detailing the conversion of CAD drawings for compatibility with a 3D printer. An overview of the components of a 3D printer is provided to assist educational institutions in utilizing and maintaining the device. In this program, educators exhibited considerable enthusiasm for mastering the usage of 3D printers, which will subsequently facilitate the execution of teaching and learning activities in the school environment. This program can be further enhanced by incorporating a comprehensive introduction to several types of 3D printers, thereby augmenting initiatives to elevate the quality of education at SMA Negeri 9 Yogyakarta.